Online Self-Presentation and Fear of Missing Out as a Predictor of Belongingness among College Students - Ribka Cassy Ulyartha Marbun; Karundeng, Miracle Jade Edith; Syene, Angel Vania; Fajanilan, Levy (12th International Scholars Conference 2025, 2026)
Social networking sites (SNSs) are essential platforms for college students to interact, communicate, and build social networks in the current digital era. However, students’ exposure to SNSs may also be detrimental to some aspects of their mental health. This study aimed to investigate the influence of online self-presentation and fear of missing out on the sense of belongingness, and the moderating role of sex and age among college students aged 18 – 24 years old in a faith-based university. A total of 350 respondents comprised the sample which were selected through a stratified random sampling technique. The study used widely used measures of the variables such as the Presentation of Online Self Scale for Adults (POSSA), the Fear of Missing Out Scale, and the Need to Belong Scale, which were administered via both paper-based questionnaires and online forms. The results suggest that students’ levels of online self-presentation (adaptable self, authentic self, and freedom of self online) were average. Similarly, students’ level of FoMO and sense of belongingness were also found as average. Further, FoMO were identified as the strongest predictors of sense of belongingness, followed by the freedom of self online.